Nodes of Contemporary Finnish Literature - Kirstinä, Leena (Studia Fennica Litteraria, 2012)
This book examines phenomena from Finnish and Finnish-Swedish literature written in the years between the 1980s and the first decade of the new millennium. Its objective is to study this interesting era of literary history in Finland and to sketch some possible directions for future development by identifying literary turning points which have already occurred.